Relative Importance of Phosphodiesterase vs. Phosphomonoesterase (Alkaline Phosphatase) Activities for Dissolved Organic Phosphorus Hydrolysis in Epi- and Mesopelagic Waters - Thomson, Blair; Wenley, Jess; Lockwood, Scott; Twigg, Isla; Currie, Kim; Herndl, Gerhard J.; Hepburn, Christopher D.; Baltar, Federico (Frontiers in Earth Science, 2020)
Marine microbes use extracellular phosphatases to hydrolyse phosphate from organic matter. Dissolved organic phosphorus (DOP) is typically present in higher concentrations than phosphate in oceanic surface waters. Yet, the fate and role of different DOP components, such as phosphomonoester and phosphodiester, are poorly understood. Most of the investigations on extracellular enzymatic hydrolysis of marine DOP have focused on phosphomonoesterase (MEA) activity (i.e., alkaline phosphatase), whereas phosphodiesterase (DEA) measurements are scarce. This limits our understanding of the ecological and biogeochemical role of DOP sources other than P-monoesters in the sea. We determined extracellular MEA and DEA activities including their cell-free fractions on a bimonthly basis over 14 months in surface and mesopelagic subantarctic waters, thus covering a wide range of phosphate availability levels (from <0.5 to 2.3 µM). We found that DEA and MEA exhibit similar hydrolysis rates in surface as well as in mesopelagic waters. The MEA : DEA ratio varied between 0.38 and 5.42 during the study period, indicating potential differences in function and/or expression among the two enzyme groups, potentially reflecting differences in the availability and/or utilization of P-monoester and P-diester pools. Interestingly, the MEA : DEA was negatively correlated to phosphate (r=-0.82, p=0.02, R2=0.67) and positively with N:P (r=0.84, p=0.02, R2=0.67), suggesting that the relative importance of DEA versus MEA is linked to inorganic P availability and the N : P ratio. DEA was also related to the N : P ratio, both at the surface and at depth, suggesting DEA alone is sensitive to changes in the N : P ratio. The majority (>70%) of extracellular MEA and DEA was found in the cell-free fraction which increased with depth. Our results indicated that DOP hydrolysis mediated by DEA in the surface as well as in dark ocean is as important as the frequently measured MEA.